Critical Ethnography as an Archival Tool: A Case Study of the Afghan Diaspora in Canada - Rokay, Moska (Archivaria, 2021)
Due to the limitations of existing archival theories and methodologies, there are few clear options that allow underrepresented and marginalized communities to represent themselves ethically, faithfully, and responsibly in their own voices in mainstream archival institutions. As a result, many of these communities lack knowledge and fundamental pedagogical resources about themselves and their history in Canada. Based on research from the author’s one-year master’s degree, this article uses a critical ethnographic framework and oral history interviews to understand the archival needs of a segment of the Afghan diaspora that has long been settled in Canada. The Afghan Canadian participants agreed that digital archives could provide a solution to the community’s dearth of knowledge and material about itself – its own histories and stories. The research demonstrates that a critical ethnographic framework can be applied as an instrument in the archives in order to understand the desires, identity-formation processes, and representations of a marginalized community to ensure faithful archival representation. RÉSUMÉ En raison des limites des théories et des méthodologies archivistiques existantes, il y a peu d’options évidentes permettant aux communautés sousreprésentées et marginalisées de se représenter de façon éthique, fidèle et responsable par le biais de leurs propres voix au sein des archives institutionnelles conventionnelles. De ce fait, bon nombre de ces communautés sont privées de connaissances et de ressources pédagogiques de base sur elles-mêmes et leur histoire au Canada. Basé sur les recherches effectuées au cours d’un programme de maîtrise d’un an, cet article utilise un cadre critique ethnographique et des entrevues d’histoire orale afin de comprendre les besoins archivistiques d’une portion de la diaspora afghane, établie depuis longtemps au Canada. Les Canadiens- Afghans participants s’accordent pour dire que les archives numériques offrent une solution à la rareté des connaissances et de matériel portant sur eux-mêmes – leur propres histoires et récits. La recherche démontre que le cadre critique ethnographique peut être un outil dans les archives pour comprendre les désirs, le processus de formation identitaire et les représentations des communautés marginalisées afin d’assurer une représentation fidèle dans les archives.